High performance lithium-ion cells using one dimensional electrospun TiO2 nanofibers with spinel cathode - Kumar, Palaniswamy Suresh (2013)
Eco-friendly, high performance lithium-ion cells (LiMn2O4/TiO2) are fabricated using electrospun one dimensional anatase phase TiO2 nanofibers. The cells deliver an initial discharge capacity of ~104 mAh g−1 (at 1 C) with an operating potential of ~2.1 V and stay stable for up to 100 cycles with limited capacity fading.